2020
DOI: 10.1101/2020.09.17.302299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Force generation by protein-DNA co-condensation

Abstract: SummaryCapillary forces are driven by interactions between liquids and surfaces1. These forces are crucial for many processes ranging from biology and physics to engineering, such as the motion of aquatic insects on the surface of water2, modulation of the material properties of spider silk3,4, and self-assembly of small objects and microstructures5. Recent studies have shown that cells assemble biomolecular condensates in a manner similar to phase separation6. In the nucleus, these condensates are thought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 41 publications
6
23
0
Order By: Relevance
“…The causal relevance of Pol II phosphorylation is supported by the application of chemical inhibitors of Pol II phosphorylation, which induces changes in cluster morphology and cluster number that are in line with predictions from our lattice simulations. In combination with previous work on Pol II liquid phase behavior 13,14 and studies showing condensation of transcription factors by wetting of DNA in vitro 23,24 , our findings in zebrafish, an embryonic model system, suggest that similar liquid phase wetting of chromatin might also occur in vivo.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…The causal relevance of Pol II phosphorylation is supported by the application of chemical inhibitors of Pol II phosphorylation, which induces changes in cluster morphology and cluster number that are in line with predictions from our lattice simulations. In combination with previous work on Pol II liquid phase behavior 13,14 and studies showing condensation of transcription factors by wetting of DNA in vitro 23,24 , our findings in zebrafish, an embryonic model system, suggest that similar liquid phase wetting of chromatin might also occur in vivo.…”
Section: Introductionsupporting
confidence: 87%
“…Formation of macromolecular clusters at genomic target regions has recently been described using a model of liquid phase condensation on polymers as microscopic surfaces 13,14,23,24 . To test whether such a model can reproduce the different cluster morphologies seen in our experiments, we implemented corresponding lattice kinetic Monte Carlo (LKMC) simulations 31,32 (for details see Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FUS-ssDNA co-condensate have liquid-like properties (see above). Capillary forces are mechanical forces that are generated by a fluid when contacting a surface (de Gennes, Brochard-Wyart and Quéré, 2004; Quail et al ., 2020). Given that self-interactions of the FUS-ssDNA polymer can generate a liquid phase, it is tempting to speculate that this can give rise to generalized capillary forces for liquid phases consisting of collapsed self-interacting polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Such condensates have been suggested to play an important role in the generation of transcriptional hubs that could coordinate the expression of several genes and mediate enhancer function (Cho et al ., 2018; Sabari et al ., 2018; Guo et al ., 2019; Henninger et al ., 2021). Recently it was shown that a pioneer transcription factor can form co-condensates together with DNA in vitro (Quail et al ., 2020). Some membrane-less compartment in the cell nucleus, such as the nucleolus, show all the features of liquid-like condensates (Brangwynne, Mitchison and Hyman, 2011; Feric et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%